The Development of the School of Spatial Analysis of W.Isard on the Basis of Economic and Supply Chain Management Models of the Petrochemical and Chemical Production Cluster - I.L. Beilin; V.V Homenko; D.D Aleeva (International Journal of Supply Chain Management, 2019)
Abstract- In the first post-war decade, studies of the problems of the regional economy were developed in many countries based on the supply chain management. Prerequisites were created for the unification of regional scientists and a new attempt to synthesize theories of spatial and regional economics. At this stage, the avant-garde role was played by an American scientist, W. Isard.Hi is first major monograph, â€œThe Placement and Economics of Space,â€ was published in which he posed the problem of eliminating the deep discrepancies that exist for more than 100 years between classical theories; accommodation and leading schools of general economic theory.W. Isard rightly criticizes all classical and neoclassical economic theories for the fact that they limited themselves to studying "a country of miracles devoid of any spatial characteristics." This was partly due to the classical placement theories, which were expounded in outdated language and with excessive simplifications of "partial equilibrium", constant coefficients, cost minimization, constant demand curves, etc. Overcoming the stereotypes of these theories, W. Isard will clothe the theory of locating production in a more general economic form. He deduced the following law: profit maximizing firms will be located; so that the marginal rates of replacement of transportation costs of goods from two different points (regions) are equal to the reciprocal of their transportation tariffs. From this condition of the first order of maximizing profit, one can derive all particular allocation theories (Tyunen, Launhardt, Weber, etc.). Further, W. Aizard links, where it is possible, the theory of location with the known theories of production, pricing, trade, etc.